PENERAPAN MENDENGARKAN MUROTTAL Q.S. AR RAHMAN TERHADAP POLA TEKANAN DARAH PADA PASIEN HIPERTENSI DI RSUD UNGARAN: THE APPLICATION OF Q.S. AR RAHMAN MUROTTAL THERAPY IN THE BLOOD PRESSURE PATTERN OF PATIENTS WITH HYPERTENSION IN RSUD UNGARAN - Luluk Rahmawati; Dwi Mulianda (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2020)
Hypertension is a medical condition in which the systole and diastole pressure abnormally elevate. Q.S. Ar Rahman Murottal is a complementary therapy for lowering blood pressure. This case study aims at describe the effect of Q.S. Ar Rahman Murottal therapy on the blood pressure pattern in patients with hypertension at RSUD Ungaran. The method of this study is descriptive. The subjects of this case study are two Moslem patients with hypertension who have no hearing problems. The data are collected through observation and measurement by using medical tools such as sphygmomanometer and stethoscope before and after the therapy. The result of this study shows that the blood pressure in Subject I decreases from 150/90 mmHg to 120/80 mmHg, while in Subject II the blood pressure decreases from 160/90 mmHg to 120/90 mmHg. It means that Q.S. Ar Rahman Murottal therapy is effective in lowering the blood pressure in patients with hypertension at RSUD Ungaran. It is hoped that this case study can be the beginning of extensive researches in Q.S. Ar Rahman Murottal in lowering the blood pressure in hypertension patients. Hopefully, Ungaran Hospital will make Q.S. Ar Rahman Murottal as an SOP to be given to hypertension as a nonpharmacological therapy for pharmacological therapy.